2019
DOI: 10.1177/1557988319832120
|View full text |Cite
|
Sign up to set email alerts
|

Enrollment Challenges: Recruiting Men to Weight Loss Interventions

Abstract: Obese men are at an increased risk of chronic disease and are far less likely than women to attempt weight loss. There is a need to successfully recruit men to weight loss clinical trials. Overweight and obese men were recruited to a 6-month, randomized, controlled weight loss trial. Initial recruitment efforts were aimed at men in the workplace with less than or equal to 2 years of college education. After unsatisfactory interest from men and businesses alike, recruitment strategy shifted to enroll men outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
(46 reference statements)
1
29
1
Order By: Relevance
“…Representativeness is rarely reported in weight loss trials, but our findings are largely consistent with a previous trial in 3 health maintenance organization (HMO) settings where enrollees were more likely to be female, non-smokers, and had a lower disease risk score [47]. There is a long history of men being under-represented in behavioral weight loss trials, [48,49] and surface-level tailoring of recruitment materials, e.g. including pictures of men as we did in this study, is likely insufficient.…”
Section: Comorbid Conditionssupporting
confidence: 87%
“…Representativeness is rarely reported in weight loss trials, but our findings are largely consistent with a previous trial in 3 health maintenance organization (HMO) settings where enrollees were more likely to be female, non-smokers, and had a lower disease risk score [47]. There is a long history of men being under-represented in behavioral weight loss trials, [48,49] and surface-level tailoring of recruitment materials, e.g. including pictures of men as we did in this study, is likely insufficient.…”
Section: Comorbid Conditionssupporting
confidence: 87%
“…Another limitation to consider is that a significantly larger number of females participated in this study compared to males. Men are notoriously difficult to recruit for nutrition related research giving rise to potentially gender-biased results [73]. Therefore, future studies should consider having an equal balance in genders or alternatively be powered to investigate effects in men and women separately.…”
Section: Discussionmentioning
confidence: 99%
“…The Game of Stones sample was more disadvantaged than most men-only weight management interventions [20,[25][26][27][28]. Disadvantage is linked to having reduced confidence and being less likely to seek health information [52], hence, recruitment strategies specifically targeting disadvantaged communities are required to recruit socioeconomically diverse samples.…”
Section: Discussionmentioning
confidence: 99%
“…For example, whilst two men-only weight-loss trials reported efficacy at 6 months; only one participant (of 65) recruited for the SHED-IT trial in Australia resided in the most disadvantaged quintile area [28], and the sample recruited for the Rethinking Eating and FITness (REFIT) intervention in the US was highly educated (83.2% university educated) [26]. Building on REFIT, the Gutbusters trial sought to recruit less educated men; but after initial poor recruitment rates, altered the inclusion criteria to include men from any educational background, resulting in another highly educated sample (80.4% university educated) [25].…”
Section: Introductionmentioning
confidence: 99%